(untitled) (Nigerian Journal of Health Sciences, 2024)
Background: Even though vaccination is one of the most efficient ways of treating infectious diseases like COVID-19, it is frequently hampered by hesitancy and resistance due to fear of certain symptoms and vaccine safety concerns. Method: The study employed a retrospective design. The population comprised Key Populations (KPs) in Nigerian One Stop Shops (OSS). Five key population (KP) groups were examined across six states. Data spanning a period of three years and four months (May 2019 to September 2022) were sourced from Heartland Alliance OSS databases. Data was analysed using IBM-SPSS version 28. Result: Among the participants, 99.3% reported no symptoms, compared to 0.7% who encountered certain symptoms after COVID-19 vaccination. Further examination based on vaccination status revealed that 81.5% of fully vaccinated KPs encountered specific symptoms, contrasting with a lower incidence of 18.4% among those who received booster doses. Fatigue (38.5%) emerged as the most prevalent post-vaccination symptoms. Notably, participants above 50 years were (AOR=1.582, 95% C1: 097 – 2.281) more likely to experience symptoms after vaccination compared to KPs under 20 years. KP categories demonstrated varying susceptibilities, with Persons Who Inject Drugs (PWID) being (AOR=4.532, 95% Cl: 3.606 – 5.696) times more likely to experience symptoms compared to Men who have Sex with Men (MSM) and KPs in prison. Female Sex Workers (FSW) (AOR=2.965, 95% Cl: 2.174-4.044) and KP’s in prisons (AOR=2.735, 95% Cl:2.010– 3.722) also exhibited elevated likelihoods of post-vaccination symptoms compared to MSM. Surprisingly, Antiretroviral therapy (ARV) increased the likelihood of symptoms (AOR=1.833, 95% Cl:1.1538-2.184). In addition, Pre-Exposure Prophylaxis (PrEP) users had a higher symptom rate than non-users (AOR=3.098, 95% Cl: 2.579-3.720). Conclusion: This study underscores the critical role of safe and effective COVID-19 vaccination among key populations in Nigeria. Vigilance in monitoring and addressing symptoms and promoting public confidence in vaccination programs should be encouraged.